Plant Protein Intake Is Not Associated with Cardiovascular Disease Risk Factors in Diabetic Patients with Chronic Kidney Disease (P08-055-19). (24th October 2019) - Moore, Alexis; Woolf, Kathleen; St-Jules, David; Popp, Collin; Pompeii, Mary Lou; Li, Huilin; Williams, Stephen; Goldfarb, David; Katz, Stuart; Sevick, Mary Ann
Abstract: Objectives: A higher percentage of protein consumed from plants may have cardiovascular benefits and be associated with lower mortality in chronic kidney disease (CKD) patients. The purpose of this study was to examine the association of self-reported dietary protein intake with cardiovascular disease (CVD) risk factors in patients with type 2 diabetes (T2D) and CKD. Methods: Baseline 3-day food records were obtained from 202 participants of an ongoing lifestyle intervention study, and analyzed using Nutrition Data System for Research (2014). Participants were categorized into tertiles based on total protein intake (<66.9 g, 66.9–92.4 g, > 92.4 g) and percent of total protein coming from plant sources (<27.9%, 27.9–37.8%, >37.8%). CVD risk factors included estimated glomerular filtration rate (eGFR), pulse wave velocity (PWV), fasting lipids (total cholesterol, LDL-cholesterol, HDL-cholesterol, triglycerides [TG]), and hemoglobin A1c [HbA1c]). Analyses of covariance examined mean differences in CVD risk factors among the tertiles, controlling for age and total energy intake. Results: The participants were 57% male, 89% non-Hispanic, 69% white, and 66 ± 9 years of age with a mean body mass index of 33.6 ± 5 kg/m 2 . Prior myocardial infarction was reported by 25(12.6%) of participants. Average daily protein intake was 83.3 ± 29.3 g (0.9 ± 0.3 g/kg body weight), with the average % of protein consumed from plant sources 34 ± 13%. There were no statistically significant differences between the total protein intake tertiles for the CVD risk factors (eGFR [ P = .36], PWV [ P = .86], total cholesterol [ P = .09], LDL-cholesterol [ P = .26], HDL-cholesterol [ P = .88], TG [ P = .88], HbA1c [ P = .82]. Additionally, there were no statistically significant differences between the % of total protein intake from plant sources tertiles for the CVD risk factors (eGFR [ P = .32], PWV [ P = .92], total cholesterol [ P = .29], LDL-cholesterol [ P = .10], HDL-cholesterol [ P = .57], TG [ P = .13], HbA1c [ P = .93]. Conclusions: Contrary to expectations, CVD risk factors did not differ among tertiles for total protein intake or % of total protein from plant sources. These findings suggest that, at baseline, dietary protein was not associated with CVD risk factors in patients with T2D and CKD. Funding Sources: National Institutes of Health (NIDDK, NINR).